Pemanfaatan Mesin Pencacah Plastik pada Bank Sampah di Salakan Bangunharjo Kabupaten Bantul - Pratiwi, Yuli; Waluyo, Joko; Saputra, Hadi; Lestari, Nidia (DHARMA BAKTI, 2024)
Recycling is one way to manage plastic waste. If recycled, plastic waste in the form of bottles, glasses or other plastic waste has a fairly high selling value. The waste bank in Salakan Bangunharjo Bantul has been quite engaged in the plastic waste processing business. One of the activities of this waste bank is to collect and sort plastic waste from the community, but it has not been maximized because of space constraints and also does not have a plastic waste shredder. Therefore, the Abdimas Team from the Department of Environmental Engineering and Mechanical Engineering, Faculty of Engineering, AKPRIND University Indonesia, designed and made a plastic waste shredding machine. The method carried out is to conduct plastic waste management training through waste banks, the use and maintenance of plastic waste shredding machines and the delivery of plastic waste shredding machines. The purpose of this service activity is so that the waste bank in Salakan can carry out the plastic waste recycling process optimally, so that it can increase the economic value of the plastic waste. The capacity of this plastic waste shredder is 20 Kg/hour using a gasoline motor as a propulsion, and has specifications of 66 cm in length, 38.5 cm in width and 80 cm in height. Based on the results of the survey using questionnaires, this service activity can be said to be successful because community members, especially members and administrators of waste banks in Salakan, have become more aware of the benefits of plastic waste sorting, the operation and maintenance of plastic waste shredders, and positively assess and agree with this community service activity.